Analysis Effect of Accrual Quality, Growth Opportunity and Gender Diversity on Firm Performance (Empirical Evidence from Listed Company in Indonesia Stock Exchange) - Imam N. Fambudi; Dara Fitriani (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The research aims to analyze the relationship of accrual quality, growth opportunity, and gender diversity to firm performance which is divided into two-equation models namely Tobin's Q and ROA with control variables firm size, firm age and leverage using multiple regression analysis methods. The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017 with a total sample of 117 companies. The results showed that accrual quality and growth opportunity had a significant positive effect on the ROA model while gender diversity had a significant negative effect on Tobin's Q.